Anlotinib as Maintenance Therapy After First-Line Chemotherapy Combined with Consolidation Radiation for Extensive-Stage Small Cell Lung Cancer - Jinbo Ma MD; Xiaoyan Ma MS; Wei Zhang MD; Shanliang Hu MS; Rukun Zang MS; Xiaolong Wu MS; Jie Song MD (Technology in Cancer Research & Treatment)
Background Small cell lung cancer is sensitive to chemotherapy and radiotherapy, but local recurrence and distant metastasis occur shortly after treatment. This study aimed to evaluate the real-world value of anlotinib as a maintenance therapy in patients with extensive-stage small cell lung cancer (ES-SCLC) after first-line chemotherapy and consolidative thoracic radiotherapy (CTRT). Patients and Methods A total of 150 patients with ES-SCLC treated with first-line chemotherapy and CTRT from April 2017 to December 2021 were retrospectively analyzed. After the completion of chemoradiotherapy, patients received anlotinib according to their desire. The primary endpoints were progression-free survival (PFS) and overall survival (OS) after the first diagnosis, and the secondary endpoints were prognostic factors and safety. Results The ORR and DCR of patients with ES-SCLC were 50.0% and 80.3%, respectively, in the anlotinib group and 42.9% and 69.0% in the no-maintenance therapy group. The 3-year OS rates were 27.6% and 12.6% in the anlotinib and observation groups (HR = 2.52, P  = 0.003), and the median OS times were 23.8 months and 15.3 months. The 3-year PFS rates were 18.2% and 8.8% in the anlotinib and observation groups (HR = 1.76, P  = 0.034) with median PFS times of 11.5 months and 8.8 months. After stratification on the basis of clinical response, patients who achieved CR plus PR after chemoradiotherapy had a longer median OS in the anlotinib and observation groups (34.0 months vs 24.8 months, HR = 2.40, P  = 0.009). There were higher incidence rates of hand–foot syndrome (27.3% vs 10.5%, P  = 0.001), gingival bleeding/hemoptysis (18.5% vs 4.8%, P  = 0.015) and rash (33.3% vs 4.8%, P  < 0.001) in the anlotinib group than in the observation group. Conclusion Maintenance therapy with anlotinib improved the survival of patients with ES-SCLC after first-line chemotherapy and CTRT. Owing to the small sample size of the real-world trial, the reliability of our study needs to be confirmed in more studies.